On Some Aspects of Legal Status of Parish Clergy of Russian Orthodox Church in the Second Half of 19th - Early 20th Centuries (Based on Material of the Central Black Еarth dioceses) - S. A. Ikonnikov (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article is devoted to the study of the legal status of the parish clergy of the Orthodox Russian Church in the second half of 19th - early 20th centuries. On the basis of archival documents and published sources, the privileges and advantages of the clergy are considered. Particular attention is paid to the analysis of the shortcomings of the legal status of clerics. The author notes the intertwining of the norms of secular and ecclesiastical law in the Russian legislation, which not always had a positive impact on the social situation of the altar servants. The analysis of the sources showed that in the post-reform period, despite the privileged status of the Church, the clergy were in factual dependence on parishioners, Church authorities, Consistory employees, officials of the crown administration. The considered documents demonstrate the discontent of the overwhelming majority of the clergy with their legal status. The article examines the measures proposed in the course of a broad public discussion aimed at improving the social and legal status of the clergy, parishes and bodies of diocesan administration. The author comes to the conclusion that in the period under review the legal status of clerics as a whole reflected the position of the Church within the Synodal system of governance, which legally turned clerics into employees of the Department of Orthodox confession.